Molecular typing and characterization of Staphylococcus aureus isolates from burn wound infections in Fujian, China - Hong, Xiaolan; Zhou, Shaobo; Dai, Xubo; Xie, Dandan; Cai, Yuanyuan; Zhao, Guimei; Li, Bin (Frontiers in Microbiology, 2023)
Background Staphylococcus aureus (S. aureus) is the most common causative agent of burn wound infection, that often leads to high morbidity and mortality. However, there is not enough knowledge about the molecular epidemiology and antimicrobial susceptibility of S. aureus isolates from burn wound infections in Fujian, China. Methods Between 2016 and 2021, 90 S. aureus isolates were collected from burn wound infections in Fujian, China, including 59 methicillin-resistant (MRSA) strains and 31 methicillin-susceptible (MSSA) strains. These were investigated for molecular characteristics, virulence genes, biofilms, and antimicrobial susceptibility. All the isolates were genotyped by multilocus sequence typing (MLST), spa typing, agr typing, and SCCmec typing. Conventional PCR was performed for the detection of virulence genes. Biofilm formation capacity was assessed by tissue culture plate assay (TCP). The antimicrobial susceptibility of the isolates was evaluated using the dilution method. Results In total, 37 sequence types (ST) and 34 Staphylococcal protein A (spa) types (including a new type named spa-t20720) were identified based on multilocus sequence typing (MLST) and spa typing, respectively. CC8-ST239-t030-agrI-SCCmecIII (57.6%,34/59) and CC7-ST7-t091-agrI (16.1%, 5/31) represented the main clone of MRSA and MSSA isolates, respectively. Antibiotic susceptibility testing identified a significant difference in resistance rates between ST239 and non-ST239 isolates (p < 0.05). Twelve virulence genes were detected, of which the most common were icaA and icaD (both 100%), followed by icaB and icaC (both 96.7%), icaR (95.6%), lukED (81.1%), lukAB (62.2%), pvl (50%), hlgBC (26.7%), and eta (4.4%). Moreover, lukAB, hlgBC, agrI, and agrIII were significantly correlated with burn severity (p < 0.05). MRSA isolates were less likely, compared with MSSA isolates, to carry pvl, lukAB, and hlgBC (p < 0.05). A new spa type, t20720, was identified that contains pvl, lukED, lukAB, hlgBC, icaA, icaB, icaC, icaD, and icaR genes and has strong biofilm formation ability. Conclusion CC8-ST239-t030-agrI-SCCmecIII and CC7-ST-7-t091-agrI were the prevalent molecular signatures of MRSA and MSSA isolates from burn wound infections in Fujian, China, respectively. The newly identified spa-t20720 isolate, which carries a wide range of virulence genes and has strong biofilm formation ability, requires special clinical attention.